DESIGNING THE TECHNICAL PARAMETERS OF THE HYDROELECTRIC POWER PLANT - Mamarasulov Qudratbek Shuxratbek o‘g‘li; Ortiqova Shaxnoza (Лучшие интеллектуальные исследования, 2024)
Abstract. In this article, the guidelines for the application hydropower plants to agriculture were considered.